Digital Single Market and coordination of social security systems – interoperability solutions at the service of social protection - Fernandes, Sophie Perez (2018)
One of the fundamental pillars to the full achievement of the Digital Single Market is the development of eGovernment/e-administration. As a key priority of the current moment of the European integration process, the implementation of the Digital Single Market has the potential to lay down the foundations for a public administration capable of providing crossborder mobility in the Single Market of the Union by means of high quality, interoperable and digital public services. To exemplify the characteristics outlined for the configuration of a public administration of the Digital Single Market, we will seek to give concrete form to the model that is emerging in a specific area of EU law which has critical importance for the European integration process – the coordination of social security systems. Its consideration allows us to test the implementation of the Digital Single Market in the public sector through digital, interoperable, and high-quality cross-border public administration.